Disiplin Hukum Dalam Pendekatan Filsafat Hukum - Syahror Adjani Rianto; Rd.Ramdan Arya Wiguna; Andi M.Afif Ananda Agung; Andika Satya Graha; Owen Rizky Alfazry Korua (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2023)
The purpose of writing this law is to develop knowledge in legal disciplines in a legal philosophy approach using library research methods. The legal discipline talks about law as a unit of knowledge that is different from other sciences, in the theory of Hans Kelsen, the originator of The Pure Theory of Law. Through an approach to legal philosophy, dissecting the parts of the law itself, there are many problems in the discussion of the law itself, such as the law is often accompanied by the sentence justice, it does not mean that the law has nothing to do with justice. Thus some of the reviews in Philosophy of Law seek the law itself.